Produção e valor nutritivo da Urochloa ruziziensis adubadas com dejeto líquido de suíno - Silva, Marinho Rocho da (2020)
Pig farming is an economic activity that stands out on the national scene, however the generation of waste as well as its destination is a matter of concern, considering the large volume generated in its production system and the problematic destination of it. The degradation of pastures in Brazil is a problem of wide scope and routine, and the use of organic residues, such as swine liquid manure (DLS) is an alternative that presents viability, by the constitution of nutrients in its composition as well as by the correct destination of that residue. On the other hand, the lack of fertilization has been one of the main causes of degradation of pastures, a fact that can be reduced by using these residues as sources of nutrients for forage plants. Given the above, the objective was to evaluate the production potential and nutritional value of Urochloa ruziziensis, in response to fertilization with DLS in two years of cultivation. The experimental design was a randomized block with five treatments and four replications. The treatments in the first year were four doses of DLS (0; 10; 20 and 30 m3 ha-1) and a mineral fertilizer (500 kg ha-1 N) with urea as source, and in the second year (0; 30; 60 and 90 m3 cut ha-1) and a mineral fertilizer (200 kg ha-1 N). Thirty days after the emergency, a uniform cut was made at a height of 15 cm and the doses were applied to each cut corresponding to each treatment. In the months of March, April, May, October, November, December 2014 and January 2015 corresponded to the cuts of the first year (7) and the months of February, March, April and May 2015, the cuts of the second year (4). In each cut, height measurements were made at 10 points, and green mass was collected at three points of 1 m2 in each plot. The samples were weighed and taken to a forced air circulation oven at a temperature of 60ºC for 72 hours. Then, the samples were ground to 1 mm and stored in airtight jars. Plant height (ALT), total dry mass production (PMS), dry matter (DM), crude protein (PB), neutral detergent fiber (NDF) and acid (FDA), digestible nutrient estimates were evaluated total (NDT), dry matter (DMS) and organic matter (DMO) digestibility, macronutrient content (N, P, K, Ca, Mg and S) and micronutrient content (Fe, Zn, Mn and Cu). Mineral fertilization in the first year provided higher plant heights, CP content, N and S extractions, and lower NDF content. There was no difference in the levels of FDA, NDT, DMS and DMO between the doses of DLS and mineral fertilization. At the dose of 30 m3 ha-1 of DLS, PMS and the extractions of P, K, Ca and Mn were equal to mineral fertilization. For Mg, Fe, Zn and Cu extractions, doses of 20 and 30 m3 ha-1 of DLS did not differ from mineral fertilization. Between the doses of DLS there was an increasing linear effect, with an increase in the treatment with a higher dose over the control treatment (0). For the variables PMS (30.89%), ALT (14.94%), PB (17%), N (53.01%), P (40.79%), K (27.84%), Ca (35.17%), Mg (29.6%), S (47.13%), Fe (31.2%), Zn (31.69%) and Mn (23.04%). In the 2nd year, mineral fertilization provided greater extraction of S compared to doses of DLS, with an increase of 52.23% over the highest dose. The dose of 90 m3 ha-1 of DLS was equal to mineral fertilization in the variables ALT and PB, while for PMS the doses of 60 and 90 m3 ha-1 of DLS were equal to mineral fertilization. In the variables NDF, FDA, NDT, DMS and DMO, they did not differ between the doses of DLS and mineral fertilization. In the extractions of N, P, K, Ca, Mg, Fe, Zn, Mn and Cu, doses of 60 and 90 m3 ha-1 did not differ from mineral fertilization. Between doses of DLS, there was an increasing linear effect with an increase in the highest dose on the control in the variables PMST (106%), ALT(39%), PB (15%), N extraction (140%), P (153%), K (147%), Ca (89%), Mg (110%), S (107%), Fe (119%), Zn (104%), Mn (106%) and Cu (101%). Dose of 90 m3 ha-1 of DLS promotes an increase in PMS and CP content, without altering NDF, FDA, NDT, DMS and DMO in addition to linearly increasing macro and micronutrients in Urochloa ruziziensis.